Hutton, Eric L., ed., Dao companion to the philosophy of Xunzi - Sung, Winnie (2020)
The seventeen essays in Dao Companion to the Philosophy of Xunzi introduce readers to Xunzi 荀子 and the Xunzi text, overview the debates in existing scholarship, and provide original analysis of various aspects of Xunzi’s thought as well as its interaction with other philosophical traditions. This is, in my view, a long-awaited volume that contains comprehensive, in-depth, and up-to-date discussions of Xunzi. What is unique about this volume is that it is the first English-language anthology that examines a wide range of philosophical themes and issues in Xunzi’s thought. It also situates Xunzi’s thought in his own pre-Qin 秦 China context and traces the influence and development of his thought in the later periods from Han 漢 to Song 宋 China, Edo 江戶 Japan, and Chosŏn 朝鮮 Korea.